Antioxidative activities of alpha-mangostin in high-fat/high-glucose diet and streptozotocin-induced insulin-resistant rodents - Gilbert Lazarus, Sean Alexander, Gabrielle Ophelia Kusuma, Kevin Wijaya, Vivian Soetikno (Journal of Applied Pharmaceutical Science, 2020)
Insulin resistance (IR), of which pathomechanism is mainly mediated by oxidative stress, leads to impaired insulin secretion and multisystem damages. Recent evidence suggests that alpha-mangostin (α-MG) is a potential candidate to ameliorate oxidative stress; hence, this study aims to evaluate the antioxidative properties of α-MG in IR-induced rats. A total of 36 male Wistar rats were divided into six groups, i.e., control, control + α-MG (200 mg/kg), IR, IR + metformin, and IR + various doses of α-MG (100 and 200 mg/kg) which were administered via oral gavage for 8 weeks. IR was induced by administering high-fat/high-glucose diet for 11 weeks followed by a single streptozotocin injection (35 mg/kg, i.p.). Malondialdehyde (MDA), superoxide dismutase (SOD), and glutathione (GSH) activities were assayed to assess the oxidative stress between groups. Welch’s analysis of variance and Kruskal–Wallis test were used to compare the data. This study demonstrated that α-MG remarkably decreased MDA and increased SOD as well as GSH activities in the heart, liver, and kidney tissues of IR model. Furthermore, α-MG also upregulated SOD activity in heart tissues in a dose-dependent manner. Besides its antioxidative effects, the administration of α-MG at 200 mg/kg was also associated with the upregulation of skeletal glucose transporter type 4 expression (2.50 ± 0.43 vs. control, 3.65 ± 0.36 ng/ml; p < 0.05). These findings suggest that α-MG yielded the potent antioxidative properties against IR rats.
Keywords: Stress, oxidative, antioxidants, alpha-mangostin, insulin sensitivity.